Determination of financial transmission right effects in transmission expansion / Muhammad Amir Abdul Hamid - Abdul Hamid, Muhammad Amir (2020)
Planning for transmission capacity in transmission expansion is crucial as any shortage could causes the generator from selling at high price location. This report presents the investigation of Financial Transmission Right (FTR) effect on transmission expansion based on investor preference. The proposed approach was solved using Grey Wolf Optimizer (GWO) and tested on three-node network. The results obtained showed that FTR are affected depends on the case of expansion.